2013
DOI: 10.1017/brimp.2013.31
|View full text |Cite
|
Sign up to set email alerts
|

Dose and Content of Training Provided to Stroke Survivors with Severe Upper Limb Disability Undertaking Inpatient Rehabilitation: An Observational Study

Abstract: Background: To retrain upper limb function after stroke, a high dose of activity-related therapy is recommended. However, observational studies indicate that the dose undertaken is minimal. While it is speculated that those with severe disability will perform less therapy, this remains to be explored.Objective: Quantify the dose and content of upper limb therapy performed by stroke survivors with severe upper limb disability during routine inpatient rehabilitation.Methods: Therapy provided by physiotherapists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
1
12
0
1
Order By: Relevance
“…Usual therapy (received by all participants) was of a high volume in this current study compared to previous studies 35 . No consistent effort was made however, to relate goals of usual therapy to SMART Arm training, limiting potential for carryover for those who received both 46 .…”
Section: Discussionmentioning
confidence: 89%
“…Usual therapy (received by all participants) was of a high volume in this current study compared to previous studies 35 . No consistent effort was made however, to relate goals of usual therapy to SMART Arm training, limiting potential for carryover for those who received both 46 .…”
Section: Discussionmentioning
confidence: 89%
“…The primary author of one study was contacted to clarify the item of investigator concealment. 26 Individual items highlighted several studies with a potentially elevated risk of bias and may have led to an overestimation of dose: three studies failed to use an independent observer to document therapy dose 30,31,35 and five studies had an inadequate sample size to make precise estimates. 26,28,29,32,35 Also, the main aim for only three out of the ten studies 30,32,34 was to document arm training dose.…”
Section: Resultsmentioning
confidence: 99%
“…27,35 Studies completed during subacute rehabilitation demonstrated a similar pattern, with a mean of four minutes within a physiotherapy session 26,28,30,33 and 11 minutes within an occupational therapy session. [29][30][31] With regards to movement repetitions, 23 to 32 activity-related arm repetitions were performed per session across both Excluded after screening title/abstract, n = 3 115…”
Section: Discussionmentioning
confidence: 99%
“…Natomiast czas aktywnej terapii ruchowej KG chorych średnio 5,6 dnia od udaru wynosił ok. 4 minuty w jednej sesji (17% całej jednostki terapeutycznej) i ok. 11 minut w sesji terapii zajęciowej (49% całej jednostki terapeutycznej) [23]. W fińskim badaniu Peurala et al wykazał, że dawka czasowa aktywności KG chorych (n=19) (średnio osiem dni od udaru) podczas fizjoterapii stanowi ok. 6 minut ćwiczeń na sesję (15% jednostki terapeutycznej) [24,25]. Australijskie doniesienia (n=32) dotyczące chorych (średnio 40 dni od udaru) mówią o braku aktywności KG podczas fizjoterapii [26].…”
Section: Wczesna Rehabilitacja Po Udarze Mózgu a Fizjoterapia Chorychunclassified
“…11 minutes during an occupational therapy session (49% of the whole therapeutic session) [23]. In the Finnish study by Peurala et al, it was noted that on average 8 days post stroke, patients (n=19) received 6 minutes of UL training per session (15% of a therapeutic session) [24,25]. Australian reports (n=32) concerning patients (an average of 40 days post stroke) revealed the lack of UL activity during physiotherapy [26].…”
Section: Wczesna Rehabilitacja Po Udarze Mózgu a Fizjoterapia Chorychmentioning
confidence: 99%